Gurgesiella dorsalifera, onefin skate - Pollom, R. (2020)
The Onefin Skate (Gurgesiella dorsalifera) is a small (to 53 cm total length) skate that occurs in the Southwest Atlantic from Rio de Janeiro to Santa Catarina State, Brazil. It is demersal on the continental slope at depths of 400–800 m. It is captured in deep-water demersal trawl fisheries, which were developed in Brazil in order to take some pressure off depleted inshore stocks. In southern Brazil, the trawl fishery began in the 1960s and entered a period of rapid expansion in the 1990s and 2000s, resulting in over 650 vessels fishing at depths of 20–1,000 m. From 2003 to 2007, this species was the second-most common discarded bycatch in southern Brazil shrimp trawls by the Spanish deep-water fleet (which comprised 68% of all deep-water trawls off Brazil during that time). This skate is also a common bycatch of the Argentine Squid fishery, which is intense and operates down to about 600 m depth. Although typically discarded, post-release mortality is suspected to be high and it is likely that fishing mortality is leading to a reduction in the population size. Overall, it is suspected that the Onefin Skate has undergone a population reduction of 30–49% over the past three generations (21 years), and it is assessed as Vulnerable A2d.